2011
DOI: 10.1007/s13213-011-0258-x
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a medium for recombinant endo-β-1,4-xylanase production by Kluyveromyces lactis using a statistical experimental design

Abstract: Kluyveromyces lactis is an excellent host for a high cell density culture, which allows high expression levels of recombinant enzymes. Nutrient composition and culture conditions affect the secretion, production level and stability of the recombinant host. Therefore, it is technologically important to formulate a medium that stimulates high cell density and enhances the desired enzyme production using K. lactis GG799. In this study, six media were initially compared, and a Plackett-Burman experimental design w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Xylanases are effectively applied in various industrial applications, including feed, food, textile, pulp, and paper. Xylanases have additionally been suggested to provide valuable possibilities for the bioconversion and biodegradation of diverse agro-industrial and processing wastes into numerous value-added products [ 104 ]. However, the presence of XIs can have a negative effect on several industrial processes in which adding microbial xylanases improves the quality of the final product [ 65 ].…”
Section: Strategies To Reduce the Effect Of Xis In Food Processing An...mentioning
confidence: 99%
“…Xylanases are effectively applied in various industrial applications, including feed, food, textile, pulp, and paper. Xylanases have additionally been suggested to provide valuable possibilities for the bioconversion and biodegradation of diverse agro-industrial and processing wastes into numerous value-added products [ 104 ]. However, the presence of XIs can have a negative effect on several industrial processes in which adding microbial xylanases improves the quality of the final product [ 65 ].…”
Section: Strategies To Reduce the Effect Of Xis In Food Processing An...mentioning
confidence: 99%
“…Xylanases (EC 3.2.1.8) have played an important role in many industrial processes and have been applied as additives to enhance the quality of baked goods, animal feeds as well as to bleach kraft pulp [1]. The xylanases are also the crucial enzymes for the depolymerization of xylan by randomly hydrolyzing the β-1,4-glycosidic bonds to produce xylooligosaccharides with different lengths, thus they have great potential commercial value.…”
Section: Introductionmentioning
confidence: 99%
“…In control samples, peak xylanase activity was measured at 5545 U L −1 on the 2nd day of incubation. In this study, it is demonstrated that the optimal productivity of the xylanase enzyme was achieved at shorter incubation times (12 h), which, as per Fuzi et al (2011), renders the medium suitable for use when seeking efficient and time-saving production.…”
Section: Medium Optimizationmentioning
confidence: 88%